Bioactive foods in promoting health : Fruits and Vegetables - Watson, Ronald R. (Academic Press, 2010)
"While everyone knows fruits and vegetables are beneficial to good health, it's increasingly seen as important to know which ones can be effective in treating specific illnesses. Bioactive Foods in Promoting Health: Fruits and Vegetables brings together experts working on the different aspects of supplementation, foods, and plant extracts, in health promotion and disease prevention. Their expertise and experience provide the most current knowledge to promote future research. Dietary habits need to be altered, for most people and the conclusions and recommendations from the various chapters in this book will provide a basis for that change. The overall goal of this book is to provide the most current, concise, scientific appraisal of the efficacy of key foods and constituents medicines in dietary plants in preventing disease and improving the quality of life. While vegetables have traditionally been seen to be good sources of vitamins, the roles of other constituents have only recently become more widely recognized. This book reviews and often presents new hypotheses and conclusions on the effects of different bioactive components of the diet, derived particularly from vegetables, to prevent disease and improve the health of various populations."--Publisher's description.